Re-skilling vocational education and training practitioners in Indonesia. (April 2020) - Fairman, B; Voak, A; Abdullah, H; Indarjo, A
Abstract: Globalisation, together with the escalating levels of internationalisation of education, is placing emerging and unfamiliar pressures on the Indonesia vocational education and training system. Increasingly, Indonesia, like many other ASEAN nations, is being challenged by the growth of employee mobility and currently, their educational institutions struggle to provide the human resource development frameworks to build a modern skilled and efficient workforce. Recognising this need to meet these urgent demands for a modern skilled and trained workforce, the Indonesian government has focused on the introduction of advanced technical and vocational education through a 'Revitalisation Program for Vocational Higher Education Institutions'. This program is designed to improve the relevance, engagement and understanding between vocational and higher education institutions with business and industry, but it often calls on international educational support. In this paper, we examine the implications of importing 'external knowhow' into the Indonesian vocational education and training sector, placing particular focus on culturally appropriate training models, the growing reliance on 'external' models of engagement, and the implications for appropriate and sustainable vocational training models. Central to this re-skilling of the vocational education and training sector, are programs that: address the human resource capability development of the educator workforce; build viable and sustainable links to industry in order to provide seamless workforce needs; explore and examine models for successful industry development; and nurture mutually beneficial 'strategic partnerships' both locally and internationally.